Ecological Spiritual Culture Is The Basis Of Cleanliness - Isaxova Shaxlo Mukhtarovna (Genius Journals, 2022)
This article is about environmental ethics, which is the direction of global bioethics, as well as the role of ecological culture in humans in nature conservation.
Keywords: Bioethics; ecoethics; environmental laws; biosphere